Analysis the motivation of tourists for staying in cities: The case study of city of Belgrade - Podovac, Milena (Anali Ekonomskog fakulteta u Subotici, 2021)
This paper presents the results of research on the tourists’ motivation for staying in the City of Belgrade. The purpose of this paper is to identify the motives for which tourists usually stay in Belgrade and to examine the existence of statistically significant differences between the motives of tourists depending on their socio demographic characteristics (gender, age, education and origin). The research sample included 250 respondents who had stayed in Belgrade. Belgrade is the most visited destination of urban tourism thanks to the quality and diversity of tourist offer, which can satisfy different motives of tourists. In order to collect primary data, a survey method was applied while descriptive statistical analysis, t-test of independent samples and one-factor analysis of variance (ANOVA) were used to process the collected data. The research findings indicate that the largest number of respondents stayed in Belgrade due to: business reasons, scientific conferences, visits to relatives and/or friends, sightseeing of the city and nightlife. Based on the theoretical analysis and results of empirical research, the recommendations for future research were also presented in the paper.